Literature-based language learning: Challenges, and opportunities for English learners - Kazi Imran Hossain (Ampersand)
Literature-based language learning (LBL) is increasingly recognized for its capacity to enhance linguistic proficiency, cultural awareness, and critical thinking in learners. This review explores the potential benefits and challenges associated with integrating literary texts into language teaching practices, emphasizing multimodal approaches, cultural relevance, and the development of language skills. While LBL promotes engagement with authentic texts, challenges arise in terms of selecting appropriate materials, addressing varying levels of student motivation, and managing linguistic complexity. This review analyzes existing theoretical discussions and current literature on LBL, offering a comprehensive evaluation of its advantages and limitations. By identifying practical strategies for overcoming common barriers, this paper contributes to the ongoing conversation on the role of literature in contemporary language education.